Chronic neutrophilic leukaemia-a rare haematological malignancy - Singh, Amandeep; Jain, Swapnil; Nawal, C. L.; Chejara, Radhey Shyam; Prakash, Vivek; Singh, Rajbeer (International Journal of Research in Medical Sciences, 2018)
Chronic neutrophilic leukaemia is a rare myeloproliferative neoplasm. It requires exhaustive workup and puts a diagnostic challenge to the clinician as well as pathologist. It should be differentiated from chronic myelogenous leukemia and reactive neutrophilia. Prognosis of the disease is poor. Here we report a case presented to us with 4 months of fatigue and fever. Investigation shows leucocytosis with predominant neutrophilia, evaluated and diagnosed as Chronic Neutrophilic Leukaemia (CNL) according to revised WHO criteria.